Imam al-Busiri - Mohd. Syukri Yeoh Abdullah; Othman Talib; Salmah Haji Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2005)
This writing explores the biography and contribution of Imam al-Busiri, the author of Burdah. This study discovers that Imam al-Busiri was a great Muslim poet with fertile imagination. He was a man of letters with evergreen characteristics because his oringinal creative work .Burdah is still being accepted and held in high esteem by a number of Muslims. His moderate life which went through several Muslim dynasties where he finally embarked on sufism, making his character more visible and his fame widespread in the history of Islamic literature of Sufism